Theoretical Systems Ecology 1979
DOI: 10.1016/b978-0-12-318750-5.50017-9
|View full text |Cite
|
Sign up to set email alerts
|

Model Structure Identification From Experimental Data

Abstract: PREFACEIn recent years there has been considerable interest in the development of models for river and lake ecological systems. Much of this interest has been directed toward the development of progressively larger and more complex simulation models. In contrast, relatively little attention has been devoted to the problems of uncertainty and errors in the field data, of inadequate numbers of field data, of uncertainty in the relationships between the important system variables, and of uncertainty in the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a qualitative, nonrigorous sense it is these changes of the estimates of unknown but constant parameters that are symptoms of the failure of individual hypotheses [Beck and Young, 1976 ;Beck, 1979a. By analogy with physical engineering structures, there has been a plastic deformation, or collapse, of a structural member (component hypothesis).…”
Section: Model Structure Identification : An Organizing Principlementioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative, nonrigorous sense it is these changes of the estimates of unknown but constant parameters that are symptoms of the failure of individual hypotheses [Beck and Young, 1976 ;Beck, 1979a. By analogy with physical engineering structures, there has been a plastic deformation, or collapse, of a structural member (component hypothesis).…”
Section: Model Structure Identification : An Organizing Principlementioning
confidence: 99%
“…Even for this more narrowly and more easily defined problem for which there are relatively systematic procedures of solution [e.g., Box and Jenkins, 1970;Soderstrom, 1977;Ha/fan et al, 1979;Hipel, 1981;Young et al, 1980], there is not necessarily any truly "objective" indicator of having identified the best model order, nor are these procedures especially effective on the data typical of environmental systems [e.g., Beck, 1979a]. Since model-order estimation is usually associated with a class III model structure, it will not be a primary concern of this review.…”
Section: Definitions Of Related Problemsmentioning
confidence: 99%
“…Since the model structure was fixed a priori in this study we have not addressed the difficult problem of model structure identification (e.g. Beck, 1979Beck, , 1980; the 'calibration' exercise here has essentially been concerned with a 'parameter estimation' problem. Nevertheless, the induced distributions of the parameter values (in the character vector) that result from the analysis can provide not only meaningful insight into the nature of the system's behaviour but also a posteriori information about the adequacy of the model structure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in problems with state variables having different physical dimensions some (subjective) form of weighting is required in the formulation of a single-valued loss function. Furthermore, it is not easy to account for uncertainty in the field data, although methods to do this have been attempted (Beck and Young, 1976;Jolankai and Szollosi-Nagy, 1978;Lewis and Nir, 1978;Beck, 1979;Di Toro and van Straten, 1979;Fedra, 1979Fedra, , 1980. Finally, however, it has to be recognized, that the assumption that a single 'best' parameter vector exists is at least questionable, especially if data uncertainty is considered, and in any case experience shows that it is extremely difficult to find such a unique vector if the number of parameters to be estimated is larger than, say, six to ten.…”
Section: Introductionmentioning
confidence: 99%
“…related to eachother, and whether information about these relationships can be identified from the in situ field data. In short, the analyst is faced with the problem of model structure identification (Beck, 1979). Put another way, and in a simpler form than the sophisticated example of the study of Saginaw Bay (Bierman et al, 1980): it is a fine idea to estimate the slope and intercept of a straight line drawn through a set of data points (i.e.…”
Section: Calibrationmentioning
confidence: 99%